Cerámica vidriada romana en los contextos altoimperiales del Campamento de León (España) - Morillo Cerdán, Ángel (2019)
The analysis of an important set of glazed Roman pottery, coming from different Early Empire contexts of the legionary fortress at León, has allowed us to reach chronological and productive conclusions, some of them endorsed through an archaeometric analysis. It has been possible to distinguish several types (skyphoi, kantharoi, calyces, pots, bottles or jars) that we have been able to assign to different production areas (Asia Minor, Campania, Lazio and, possibly, Hispania) that cover a chronological range between the Augustan period and the 1st half of the II century AD. The highest concentration of glazed pottery in the stratigraphic contexts in the city of León belong to the Augustan and Julio-Claudian Legio VI fortified military camp, decreasing considerably after the establishment of the Legio VII Gemina in 74 AD.